IMPROVEMENT OF LISTENING SKILL ON SHORT STORIES BY APPLYING MIND MAPPING - Intan Kustyarini; Hadi Mulyono; Fadhil Purnama Adi (Universitas Sebelas Maret, 2018)
Based on the observation result the listening skill on short stories of students class V of SDN Sigit II,Tangen, Sragen in academic 2017/2018 still low. Students experience problems on concentration and remember the contents of short stories. This research aims to:(1) apply Mind Mapping to improve listening skill on short stories, and (2) to describe the precise steps of Mind Mapping to improve listening skill on short stories.This research is clasroom action research (CAR) conducted during two cycles. Each cycles consists of four stages, there are planning, acting, observing, and reflecting. The subject of this research is fifth grade students of SDN Sigit II. Technique of data collecting used observation, interviews, and documentation. The validity technique used were content validity, triangualtion of techniques and triangulation of source. Technique of the data analysis used is interactive analysis. Result of this research indicate that listening skill on short stories of students class V of SDN Sigit II from preaction until cycle II has increased by 86,6%. The conclusion of this research are: (1) the implementation of Mind Mapping can improve the listening skill of short stories of fifth grade students at SDN Sigit II,and (2) discribed the precise step of Mind Mapping to improve listening skill on short stories